2021
DOI: 10.3390/biom11050763
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms of the Renin-Angiotensin-Aldosterone System as Risk Factors for the Development of In-Stent Restenosis in Patients with Stable Coronary Artery Disease

Abstract: This study investigated the renin-angiotensin-aldosterone system (RAAS) gene polymorphisms as possible genetic risk factors for the restenosis development in patients with drug-eluting stents. 113 participants had coronary artery disease and underwent stenting. The control group consisted of 62 individuals with intact coronary arteries. Patients were divided into two groups: with in-stent restenosis (ISR) and without it. The patients with ISR were classified into subgroups by the terms of the restenosis develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…Our nding was in agreement with that of (Azova et al 2021), who found that the increased frequency of the D allele and DD genotype and decreased frequency of the I allele and ID genotype were found in CAD patients compared to healthy subjects (P = 0.004). Our study was supported by another study by Abdel-Aziz et al (2014), who observed that the ACE DD genotype and D allele were associated with ESRD as risk factors for ESRD in the Egyptian population, while the distribution of the ACE ID genotype and I allele frequency were signi cantly decreased.…”
Section: Resultssupporting
confidence: 93%
“…Our nding was in agreement with that of (Azova et al 2021), who found that the increased frequency of the D allele and DD genotype and decreased frequency of the I allele and ID genotype were found in CAD patients compared to healthy subjects (P = 0.004). Our study was supported by another study by Abdel-Aziz et al (2014), who observed that the ACE DD genotype and D allele were associated with ESRD as risk factors for ESRD in the Egyptian population, while the distribution of the ACE ID genotype and I allele frequency were signi cantly decreased.…”
Section: Resultssupporting
confidence: 93%
“…In our study, the minor allele frequency of these SNPs were comparable to previous reports in Thai, 25 and Chinese 26 populations, but lower than those found in European populations. 27 We found that the variant alleles T (for AGT rs699) and C (for AGTR1 rs5186) were associated with higher BMI, HbA1C and TG levels compared with the wild-type alleles. The interaction between obesity, activation of the RAS, and hypertension has been mentioned in several experimental studies.…”
Section: Discussionmentioning
confidence: 72%
“…These include polymorphisms in the genes of the haemostatic system such as Platelet glycoprotein IIIa and the P2Y 12 receptor. 11 Interestingly, resistance to the drugs eluted from stents seems to occur in genetically predisposed patients as well. 11 …”
Section: Predisposing Factors For In-stent Restenosismentioning
confidence: 99%